Editorial: Painting by numbers: using modern approaches to analyse and visualise clinical and research data. (October 2015) - Coghill, David
Abstract A broad range of modern mathematical and statistical approaches alongside vastly increased computing power have opened up new posibilities for the management and analysis of research data. These approaches have allowed researchers to link data from large public registries and then explore these very large and complex datasets. Machine learning approaches that can both learn from and make predictions about data are helping us move closer to a personalised medicine approach. These advances in data management and analysis have been mirrored by the development of various innovative, creative and informative visualisation tools and approaches that offer the researcher fantastic possibilities to improve the clarity of their presentations and increase the impact of their research. In order to make the best use of these opportunities it will be important to ensure that we are more consistent in bringing the right kind of skills into our research teams at the beginning of the process rather than turning to them as an afterthought at the end of the process.